2020
DOI: 10.1038/s41467-019-13997-3
|View full text |Cite
|
Sign up to set email alerts
|

Macropinocytosis drives T cell growth by sustaining the activation of mTORC1

Abstract: Macropinocytosis is an evolutionarily-conserved, large-scale, fluid-phase form of endocytosis that has been ascribed different functions including antigen presentation in macrophages and dendritic cells, regulation of receptor density in neurons, and regulation of tumor growth under nutrient-limiting conditions. However, whether macropinocytosis regulates the expansion of non-transformed mammalian cells is unknown. Here we show that primary mouse and human T cells engage in macropinocytosis that increases in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…As for B cells, T cells have not traditionally been considered candidates for active macropinocytosis. However, recently, both primary mouse and human CD4 + and CD8 + T cells have been shown to exhibit significant basal levels of macropinocytosis and, moreover, the basal levels are increased upon cell activation [68]. Treatment with EIP-amiloride not only blocks macropinocytosis by non-activated and activated T cells, but also reduces mTORC1 activation and T cell growth [68].…”
Section: B Cells and T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for B cells, T cells have not traditionally been considered candidates for active macropinocytosis. However, recently, both primary mouse and human CD4 + and CD8 + T cells have been shown to exhibit significant basal levels of macropinocytosis and, moreover, the basal levels are increased upon cell activation [68]. Treatment with EIP-amiloride not only blocks macropinocytosis by non-activated and activated T cells, but also reduces mTORC1 activation and T cell growth [68].…”
Section: B Cells and T Cellsmentioning
confidence: 99%
“…However, recently, both primary mouse and human CD4 + and CD8 + T cells have been shown to exhibit significant basal levels of macropinocytosis and, moreover, the basal levels are increased upon cell activation [68]. Treatment with EIP-amiloride not only blocks macropinocytosis by non-activated and activated T cells, but also reduces mTORC1 activation and T cell growth [68]. These findings suggest a model whereby macropinocytosis mediates uptake of amino acids required for activation of mTORC1 and as a result, growth of T cells [68].…”
Section: B Cells and T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of PA binding that we measured was likely due to macropinocytosis. Recent studies have demonstrated that non-professional phagocytes, such as B cells and T cells, also perform macropinocytosis [82,83]. Therefore, it is likely that NK cells and NKT cells can also sample their environment via this internalization mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Macropinocytosis can be stimulated by growth factors in many cell types 110 , yet can be constitutive in RAS-mutant cancer cells 117 and some subsets of MΦ 118 and DCs 110 . Macropinocytosis mediates immune cell functions such as antigen scavenging and presentation by MΦ and DCs 118 , chemotactic migration of neutrophils 119 , and proliferation of T cells 120 . Macropinocytosis in particular has been shown to mediate uptake of nanomaterials, including lipid nanoparticles (LNPs) 121 and silica-based nanoparticles 122 .…”
Section: Mechanisms Of Materials Uptake By Phagocytesmentioning
confidence: 99%